Combustion behaviour and mechanism of TC4 and TC11 alloys. (15th May 2020) - Shao, Lei; Xie, Guoliang; Liu, Xinhua; Wu, Yuan; Yu, Jiabin; Hao, Zifan; Lu, Wanran; Liu, Xiao
Highlights: The burning velocity of TC4 and TC11 at the same pressure increases with longer time. The burning velocity of TC4 is faster than that of TC11 at higher oxygen pressures. The enrichment of elements leading to the different burning velocity of TC4 and TC11. The peritectic reaction is considered a key factor promotes the burning velocity. Abstract: The combustion behaviour and kinetics of TC4 and TC11 alloys are studied by non-isothermal oxidation and promoted ignition combustion tests herein. The burning velocity of TC4 is higher than that of TC11 under oxygen pressures of 0.3 MPa and 0.4 MPa. The peritectic reaction of liquid phase+α phase→TiO, is confirmed during combustion as the determining factor that promotes the burning velocity. The burning velocity of two alloys is significantly influenced by the enrichment and distribution behaviour of alloyed elements close to interface of melting zone and matrix, i.e., V for TC4 and Mo, Zr, Si for TC11.